Formulasi dan Uji Stabilitas Fisik Sediaan Lip Balm Ekstrak Etanol Buah Coppeng (Syzigium cumini) Sebagai Antioksidan - fadila, nikma (Program Studi Farmasi Universitas Mandala Waluya, 2024)
ABTRACT Lips are a sensitive part of the face, unlike other skin which has protection, lips do not have protection. When the air is too hot or too cold, lips become dry, chapped, and painful. Therefore, you need an alternative to care for your lips, namely by using lip balm or lip moisturizer made from natural ingredients. A natural ingredient that is rich in antioxidants is coppeng fruit (Syzigium cumini). Anthocyanin compounds, phenolic acids, flavonoids and tannins of coppeng fruit (Syzigium cumini) are active compounds that function as antioxidants. Therefore, lip balm is made from coppeng fruit as an antioxidant to treat lip problems. The aim of this research is to determine the physical properties and at what concentration the coppeng fruit extract (Syzigium cumini) lip balm preparation functions as an antioxidant agent, whether F1, F2 or F3. The antioxidant activity test was carried out using the DPPH method. The results of the research showed that in the organoleptic test F0, F1, F2 and F3 met the requirements, namely semi-solid dosage form, the color of F1 was light purple, F2, F3 was dark purple and had a distinctive vanilla aroma. All preparations showed homogeneous results. The average pH test of the preparation was 5.25, the average adhesion test was 5.76/second, the irritation test on F0, F1, F2 and F3 did not irritate all respondents and the most preferred hedonic test was F1. In the antioxidant activity test, the IC50 value for F1 was 86.63989 µ/ml in the strong category, F2 was 49.3719 in the µ/ml category and F3 was 4.603502 in the very strong category. Key words: lip balm preparation, coppeng fruit, antioxidant agent